Experimental study on the cyclic behaviors of an innovative lead-viscoelastic coupling beam damper (LVCBD) - Fang, X.; Zhou, Y.; Bi, Kaiming; Hao, Hong; Wang, T. (2023)
Previous researches showed that the replaceable coupling beam damper (RCBD) can effectively enhance the seismic performance of shear wall structures. However, the extensively studied metallic-type RCBD has poor fatigue performance, while the viscoelastic-type RCBD is sensitive to the loading frequency. To overcome the drawbacks of the RCBD mentioned above, this paper proposes a novel RCBD, i.e., the lead-viscoelastic coupling beam damper (LVCBD), which is not only independent of the loading frequency, but also has better fatigue performance with good energy dissipation capacity. The proposed LVCBD mainly consists of three components, i.e., the lead rods, composite viscoelastic layers and steel plates. Taking advantages of the hyper-elasticity property of rubber and the dynamic recrystallization capability of lead, the combined effects from the rubber and lead make the LVCBD reusable after a severe earthquake, and facilitate the post-earthquake recovery with less or without replacement of the RCBD. To examine the performance of the proposed novel damper, three specimens were manufactured and cyclic loading tests were carried out. The influences of the loading amplitude, loading frequency and fatigue loading on the mechanical properties of the specimen were systematically investigated and discussed. Experimental results indicated that the LVCBD showed a favorable deformation capability, frequency-independent performance, fatigue resistance and stable energy dissipation capacity under cyclic loading.